The effect of public health educational campaign regarding antibiotic use and microbial resistance on knowledge, attitude, and practice in the Iran - Mohadeseh Khoshgoftar; Fereshteh Zamani-Alavijeh; Nazila Kasaian; Kiana Shahzamani; Soodabeh Rostami; Zari Nakhodian; Asiyeh Pirzadeh (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: The aim of the present study was to show the effect of public health educational campaign regarding antibiotic use and microbial resistance on knowledge, attitude, and practice of people in Isfahan. MATERIALS AND METHODS: This quasi-experimental study was conducted in October 2019 on the public population in Isfahan (a city in the center of Iran). Simple random sampling was done in ten urban areas.). A total of 708 people participated in the study. For assessing the knowledge, attitude, and practice a related researchers-made questionnaire was used in the present study. Finally, data were entered into SPSS (20) and analytical statistics including paired t-test were used. The statistical significance level was considered <0.05. RESULTS: The majority of participants in this study were female 434 (61.9%) and the rest of them were male. The mean ± standard deviation of age was 31.68 (11.11), range of 11-67. More than 50 present of participants had a Bachelor's degree (37.7%) and diploma (27.7%). Most individuals were self-employed 277 (43.1%). About the type of marriage, 54.89% were single and others were married. Results showed that the mean of knowledge and attitude was increased after the intervention (P < 0.05). CONCLUSION: Increase knowledge between people, adherence to treatment and minimizes healthcare costs, however, "antibiotics are misused so often because of the belief that these are benign drugs. In the absence of urgent corrective and protective actions, the world is heading towards a postantibiotic era, in which many common infections will no longer have a cure and once again, kill unabated.